Effect of co-substrate feeding on methane yield of anaerobic digestion of Chlorella vulgaris - Rétfalvi Tamás (JOURNAL OF APPLIED PHYCOLOGY, 2016)
Microalgal production has many advantages over the use of terrestrial plants; therefore, increases in the use of microalgae for energy production can be expected. Algal biomass can be processed anaerobically to methane; however, the unfavorable C/N ratio of the substrate may have an inhibitory effect. The impact of the application of used cooking oil, maize silage, and mill residue on anaerobic co-digestion of the microalgal Chlorella vulgaris was studied in semi-continuous, laboratory-scale digestion. During the full period of the trial involving anaerobic digestion of algae in the case of mono-digestion and co-digestion with used cooking oil, maize silage, and mill residue, the volumetric methane yields were 0.38 ± 0.07, 1.56 ± 0.26, 1.19 ± 0.18, and 1.16 ± 0.13 L L−1, respectively. Trials were carried out to determine the long-term effect of the total solid (TS) content of substrates (co-digestion of C. vulgaris and used cooking oil at 3.8 and 7.2 % of TS, respectively). Both designs could be increased to 5.5 g VS L−1 d−1, but a higher TS% resulted in increased methane production and a longer period of decline in the methane yield due to washout. The sharp decrease in methane content at the end of 90 days was accompanied by a reorganization of the methanogenic archaeal community. © 2016 Springer Science+Business Media Dordrecht